The image of the Ukrainian military in 2022-2024 and the connective principle of its formation - Zakharchenko, Artem; Luzan, Yevhen; Machula, Anhelika; Fursenko, Maryna (Current Issues of Mass Communication, 2025)
This study validates the hypothesis that the image of a Ukrainian fighter is predominantly shaped by social media, thereby underscoring its connected nature. For an in-depth study of the transformation of the image of a fighter, we used a combination of quantitative discourse analysis and qualitative narrative analysis. The study shows how, in less than 3 years, the image of military representatives has undergone profound narrative transformations, including tonality adjustments: if in the first months after February 24, 2022, the most popular statement was the statement of valor, efficiency and professionalism of the military, then in the future attention increased to negative features: the Soviet way of thinking, neglect of preparation or risks, toxicity of communication and methods of work, etc. The study of the authors of such judgments made it possible to assert that the image of a fighter in social networks largely depends on which users at this moment are more willing to form this image, as well as on important social events that trigger its discussion.